Roles of BTLA in Immunity and Immune Disorders - Ning, Zhaochen; Liu, Keyan; Xiong, Huabao (Frontiers in Immunology, 2021)
B and T lymphocyte attenuator (BTLA) is one of the most important cosignaling molecules. It belongs to the CD28 superfamily and is similar to programmed cell death-1 (PD-1) and cytotoxic T lymphocyte associated antigen-4 (CTLA-4) in terms of its structure and function. BTLA can be detected in most lymphocytes and induces immunosuppression by inhibiting B and T cell activation and proliferation. The BTLA ligand, herpesvirus entry mediator (HVEM), does not belong to the classic B7 family. Instead, it is a member of the tumor necrosis factor receptor (TNFR) superfamily. The association of BTLA with HVEM directly bridges the CD28 and TNFR families and mediates broad and powerful immune effects. Recently, a large number of studies have found that BTLA participates in numerous physiopathological processes, such as tumor, inflammatory diseases, autoimmune diseases, infectious diseases, and transplantation rejection. Therefore, the present work aimed to review the existing knowledge about BTLA in immunity and summarize the diverse functions of BTLA in various immune disorders.